Нові дані щодо скіфських золотих аплікацій одягу з курганів біля с. Ольгине Херсонської області - Ліфантій, О.В. (Археологія і давня історія України, 2020)
Нещодавно відкриті дані змушують внести корективи у вже закріплені в літературі уявлення
про аплікації одягу, знайдені під час розкопок групи
курганів біля с. Ольгине Горностаївського району
Херсонської області. Ця публікація покликана усунути прикру плутанину та, можливо, уточнити
дату окремих поховань курганної групи. Recently revealed data considering gold appliqués
series, forced to correct notion, which has already fastened
in literature. These artefacts were found during
an excavation of a group of barrows near Olhyne
village, Hornostaivskyi district, Kherson Oblast. The
research was conducted in 1990 by the Kherson Archaeological
Expedition led by Anatolii Kubyshev. This
publication aimed to eliminate unfortunate confusion
and to clarify the date of some graves in the described
burial ground.
Thus, two garment appliqués, preserved in Archaeological
Storage of Institute of Archaeology of National
Academy of Sciences of Ukraine, that have no provenance
information were identified. These two pieces
were not published before. Due to a comparison of the
Archaeological report and analysis of Storage documentation
data, I have managed to find their place of
finding.
As shown in the article, the openwork appliqué in
a form of two-bodied Sphinx was part of headdress
decorum from the central grave of Bratoliubivka barrow
(the main and biggest mound in the group). One
rectangular-shaped plaque with a depiction of lying in
crouched pose griffin was found in the grave 5 of the
same barrow. In this inlet tomb the wealthy Scythian
warrior was buried. The construction time of the
barrow and inlaid grave 5 lay in second — early third
quarter of the 4th century BCE.
Twelve rectangular appliqués with an image of a
half-recumbent griffin with crescent-shaped wings
were found in the grave 4 barrow 1 of Olhyne group.
Previously only one plaque of this series was wrongly
published as find from the grave 5 of Bratoliubivka
barrow. This unfortunate mistake is now corrected. At
the same tomb, 52 rectangular appliqués with the depiction
of a lion attacking a doe were found. Therefore,
at well-preserved woman grave 4 of barrow 1 near Olhyne
village fully decorated hat and veil were placed.
This tomb was probably constructed in the second —
early third quarter of the 4th century BCE. Considering
the modesty of this grave goods, one can only imagine
how bright the appliques of a ceremonial garment from
the central grave of Bratoliubivka barrow were.